Revisiting targeted therapy and immunotherapy for advanced cholangiocarcinoma - Du, Jiajia; Lv, Xing; Zhang, Zunyi; Huang, Zhiyong; Zhang, Erlei (Frontiers in Immunology, 2023)
Cholangiocarcinoma (CCA) is a rare and aggressive type of malignant tumor. In the past few years, there has been an increase in the incidence of CCA. Surgery is the only effective treatment but is only suitable for a small percentage of patients. Comprehensive treatment is the normal therapy for terminal CCA patients, depending basically on gemcitabine and cisplatin combination chemotherapy. In the past decade, the emergence of next-generation sequencing technology can be used for the identification of important molecular features of CCA, and several studies have demonstrated that different CCA subtypes have unique genetic aberrations. Targeting fibroblast growth factor receptor (FGFR), isocitrate dehydrogenase (IDH) and epidermal growth factor receptor 2 (EGFR2) are emerging targeted therapies. In addition, researches have indicated that immunotherapy has a key function in CCA. There is ongoing research on programmed cell death protein 1 inhibitors (PD-1), chimeric antigen receptor T cells (CAR-T) and tumor-infiltrating leukocyte (TILs). In this study, it is hypothesized that targeted therapy, immunotherapy, and conventional chemotherapy in CCA had certain mechanistic links, and the combination of those can greatly improve the prognosis of advanced CCA patients. This study aimed to review the research progress of targeted therapy and immunotherapy for CCA.